Neoliberalism : a very short introduction - Steger, Manfred B., 1961-; Roy, Ravi K., 1969- (Oxford : Oxford University Press, 2021)
In its heyday in the late 1990s, neoliberalism emerged as the world's dominant economic paradigm. But the global financial crisis of 2008-2009 fundamentally shocked a globalized economy built on neoliberal assumptions. This introduction examines the origins, core claims, & considerable variations of neoliberalism.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 7, 2021).
Keywords: Neoliberalism